Does occupational exposure to anesthetic gases lead to increase of pro-inflammatory cytokines? - Chaoul, Maurício Martins [UNESP]; Braz, José Reinaldo C. [UNESP]; Lucio, Lorena Mendes C. [UNESP]; Golim, Marjorie de Assis [UNESP]; Braz, Leandro Gobbo [UNESP]; Braz, Mariana Gobbo [UNESP] (Inflammation Research : Official Journal Of The European Histamine Research Society ... [et Al.], 2015)
There is great concern about the possible harmful effects of exposure to volatile anesthetics. The current study aimed at evaluating, for the first time, the effects of occupational exposure to anesthetic gases on physicians who work in operating rooms, by determining several inflammatory cytokines. Plasma inflammatory cytokines (IL-1β, -6, -8, -10, -12, TNF-α) were investigated in 30 individuals who were allocated into two groups of 15: the exposed group, consisting of operating room medical personnel exposed to a mixture of anesthetic gases for 3 years, and a control group composed of medical personnel not exposed to anesthetic gases. The concentrations of volatile anesthetics were measured in the operating room by means of an infrared portable analyzer Our findings suggest an increase of the pro-inflammatory IL-8 (p < 0.05) in medical personnel exposed to high concentrations of anesthetic gases, even for a relatively short period.
Keywords: Anesthetics; Cytokines; Occupational exposure; Toxicity